2016
DOI: 10.1007/s00264-016-3167-6
|View full text |Cite
|
Sign up to set email alerts
|

Total knee replacement with tibial tubercle osteotomy in rheumatoid patients with stiff knee

Abstract: Tibial tubercle osteotomy during TKA in patients with RA and stiff knee is technically demanding yet proved to be effective in improving post-operative range of movement and minimising the complication of patellar ligament avulsion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Similarly, in a study by Eid et al, a case of DVT was reported in RA patients after total knee replacement. 13 Also, two cases of nonunion without translation were found; restoration was not required in the final follow-up.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, in a study by Eid et al, a case of DVT was reported in RA patients after total knee replacement. 13 Also, two cases of nonunion without translation were found; restoration was not required in the final follow-up.…”
Section: Discussionmentioning
confidence: 84%
“…Twenty-one articles were excluded from the meta-analysis of TTO because they did not include a control group ( Table 5 ) [ 5 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. For reattachment osteotomy, most authors used cerclage wires [ 56 , 64 , 67 , 68 , 69 , 70 , 73 , 74 , 75 , 77 ], the second most common type of fixation were screws [ 62 , 63 , 65 , 66 , 70 , 71 , 76 ] and only two studies reported suture repair [ 72 , 78 ]. TTO approach was applied in both primary TKA, for knees with severe valgus deformity [ 69 , 73 , 76 , 77 ], patella disease [ 62 , 65 , 74 ] or revision surgery (aseptic or septic) [ 63 , 64 , 65 ,…”
Section: Resultsmentioning
confidence: 99%
“…To prevent these complications, an additional procedure may be added to the usual arthrotomy. Ahmed et al reported good results of TKA using a tibial tubercle osteotomy in patients with rheumatoid arthritis [ 11 ]. Twenty-three knees with a flexion contracture of ≥ 15º and/or < 75º range of flexion were treated and showed a good result.…”
Section: Discussionmentioning
confidence: 99%